2018
DOI: 10.1016/j.jalz.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the biological pathways involved in early features of Alzheimer's disease in the Rotterdam Study

Abstract: Our study suggests that the clinical spectrum of early AD pathology is explained by different biological pathways, in particular, the endocytosis, clathrin/AP2 adaptor complex, and immune response pathways, that are independent of apolipoprotein E (APOE).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 77 publications
3
45
1
Order By: Relevance
“…Ephrin type‐A receptor 1 (EPHA1) belongs to the eph receptor subfamily that is the largest family of receptor tyrosine kinases, mediating axonal guidance, synaptic plasticity, and cell‐to‐cell communication in the central nervous system (CNS) . Moreover, EPHA1 can modulate leukocyte extravasation, chemotaxis, and inflammatory cell migration . Indeed, ample evidence has implicated the involvement of EPHA 1, as well as MS4A4A and TREM2 listed below, in the immune module of AD .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ephrin type‐A receptor 1 (EPHA1) belongs to the eph receptor subfamily that is the largest family of receptor tyrosine kinases, mediating axonal guidance, synaptic plasticity, and cell‐to‐cell communication in the central nervous system (CNS) . Moreover, EPHA1 can modulate leukocyte extravasation, chemotaxis, and inflammatory cell migration . Indeed, ample evidence has implicated the involvement of EPHA 1, as well as MS4A4A and TREM2 listed below, in the immune module of AD .…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Moreover, EPHA1 can modulate leukocyte extravasation, chemotaxis, and inflammatory cell migration. [32][33][34] Indeed, ample evidence has implicated the involvement of EPHA1, as well as MS4A4A and TREM2 listed below, in the immune module of AD. 22,35,36 As previously described, 37 we observed no aberrant EPHA1 expression in the PFC region of AD patients, neither in the hippocampus.…”
Section: Zyx and Epha1 Gene At 7q34-7q35mentioning
confidence: 99%
“…Previous studies showed that polygenic risk score of AD not only associated with increased risk of AD, but also with neuropathological hallmarks of AD, lifetime risk and the age at onset in both APOE ε4 carriers and non-carriers. [28,29,[48][49][50][51][52] We now add that the PRS for AD also associates with escaping AD at extremely old ages. This adds further importance to the potentiality of using PRS and APOE genotype in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…However, the degree to which pathways functionality may contribute to the individual risk can be studied with pathway-specific polygenic risk scores (PRS). [28,29] In a typical polygenic risk score, the effect-sizes of all genetic variants that significantly associate with a trait are combined. [30] In a pathway-specific PRS, however, additional information is necessary, namely: (i) the association of genetic variants to genes, and (ii) the association of genes to pathways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation